Switch : how to change things when change is hard. - Heath, Chip, 1963-; Heath, Dan, 1973- (London : Random House, 2010)
We all know that change is hard. It's unsettling, it's time-consuming, and all too often we give up at the first sign of a setback. But why do we insist on seeing the obstacles rather than the goal? This is the question that bestselling authors Chip and Dan Heath tackle in their compelling and insightful new book. They argue that we need only understand how our minds function in order to unlock shortcuts to switches in behaviour. Illustrating their ideas with scientific studies and remarkable real-life turnarounds - from the secrets of successful marriage counselling to the pile of gloves that transformed one company's finances - the brothers Heath prove that deceptively simple methods can yield truly extraordinary results.